(untitled) (Journal of Educational Sciences, 2025)
Career guidance in the framework of preschool education is the formation of a child’s ability for successful career development, and is also an important aspect of the formation of skills necessary for self–awareness. Taking into account that one of the most important components of the child’s socialization process is his professional self–determination, that is, the process of conscious and independent choice of a professional path, professional self-determination is not a one-time event, but a problem of a person’s entire life, and it undoubtedly begins in preschool childhood. Therefore, the relevance of the presented research work and its compliance with the requirements of today are beyond doubt. The authors conducted a comprehensive analysis and drew conclusions, making extensive use of research papers and theoretical material related to research work. In particular, in today’s conditions of inclusive education, they tried to justify the importance of early involvement of preschoolers with ASD (with mental retardation) in the profession. The necessity and importance of early professional orientation of children with special educational needs in preschool organizations are formulated in such children with the formation of specific visual representations of various professions. It has been proven by the experimental work carried out that this contributes to the expansion of their knowledge and the formation of a positive attitude and respect for work. It was also found that through early career guidance for preschoolers with special educational needs, it creates great opportunities for preparing children for life in a modern, rapidly changing society. Key words: preschooler, vocabulary, mental retardation, laptop technology, early career guidance.